2020
DOI: 10.3390/e22080877
|View full text |Cite
|
Sign up to set email alerts
|

Role of Entropy in Colloidal Self-Assembly

Abstract: Entropy plays a key role in the self-assembly of colloidal particles. Specifically, in the case of hard particles, which do not interact or overlap with each other during the process of self-assembly, the free energy is minimized due to an increase in the entropy of the system. Understanding the contribution of entropy and engineering it is increasingly becoming central to modern colloidal self-assembly research, because the entropy serves as a guide to design a wide variety of self-assembled structures for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 110 publications
(127 reference statements)
0
22
0
Order By: Relevance
“…Similar, though more limited, ribosome associations were previously observed in attack phase, particularly in a B. bacteriovorus mutant with an even more tightly condensed nucleoid than wild-type cells (Borgnia et al, 2008; Butan et al, 2011), and in some attack-phase cells in this study. One possibility for this ribosome lattice is that it is a depletion effect resulting from entropic forces encouraging large objects to aggregate on a surface (Asakura and Oosawa, 1954, 1958; Rocha et al, 2020). However, we did not observe the effect on other cell surfaces such as the inner membrane, nor in other stages of the cell cycle, so we think this unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Similar, though more limited, ribosome associations were previously observed in attack phase, particularly in a B. bacteriovorus mutant with an even more tightly condensed nucleoid than wild-type cells (Borgnia et al, 2008; Butan et al, 2011), and in some attack-phase cells in this study. One possibility for this ribosome lattice is that it is a depletion effect resulting from entropic forces encouraging large objects to aggregate on a surface (Asakura and Oosawa, 1954, 1958; Rocha et al, 2020). However, we did not observe the effect on other cell surfaces such as the inner membrane, nor in other stages of the cell cycle, so we think this unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…In what follows, a select few of the applications of fluctuation theorems are summarized and discussed. Micro-sized and nano-sized machines that are primarily entropy-driven can be realized in principle for a myriad of medical and industrial applications [43], [44]. More recently, significant advances made in the area of stochastic thermodynamics have shown that in far-from-equilibrium classical systems, random fluctuations are naturally constrained by the rate of entropy production through certain thermodynamic uncertainty relations [45]- [48].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the cumulative contributions of physicists and mathematicians, such as Nikolai Lobachevsky (1792–1856), Hendrik Antoon Lorentz (1853–1928), Jules Henri Poincaré (1854–1912), Max Karl Ernst Ludwig Plank (1858–1947), Hermann Minkowski (1864–1909), Marie Salomea Skłodowska Curie (1867–1934), Albert Einstein (1879–1955), Amalie Emmy Noether (1882–1935), Erwin Rudolf Josef Alexander Schrödinger (1887–1861), Wolfgang Ernst Pauli (1900–1958), Werner Karl Heisenberg (1901–1976), and Paul Adrien Maurice Dirac (1902–1984), the concept of space experienced a dramatic transformation, from the classical Euclidean to the modern space-time continuum, reflecting the significance of the chirality concept [ 103 , 104 , 105 ]. In parallel, the enormous progress in our understanding of the significance of molecular chirality was made by Jean-Baptiste Biot (1774–1862), Louis Pasteur (1822–1895), Joseph Achille Le Bel (1847–1930), Jacobus Henricus van’t Hoff (1852–1911), Hermann Emil Louis Fisher (1852–1919), and many others.…”
Section: Epiloguementioning
confidence: 99%
“…As a result, it becomes clear that chirality, entropy, and energy are entangled parameters of the physical and chemical objects driving their spatial behavior, playing particularly important roles in protein folding and structural dynamics. The entropy of the bio-molecular system can be partitioned into energy-dependent components: translational, rotational, orientational, and vibrational [ 105 ]. It is notable that PhTs between enzyme functional states are usually connected to conformational changes, involving electron or proton transport (spin transport) and directional shifts of a group of atoms.…”
Section: Epiloguementioning
confidence: 99%